2016
DOI: 10.1038/nplants.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the evolution of the Solanaceae from the parental genomes of Petunia hybrida

Abstract: Petunia hybrida is a popular bedding plant that has a long history as a genetic model system. We report the whole-genome sequencing and assembly of inbred derivatives of its two wild parents, P. axillaris N and P. inflata S6. The assemblies include 91.3% and 90.2% coverage of their diploid genomes (1.4 Gb; 2n = 14) containing 32,928 and 36,697 protein-coding genes, respectively. The genomes reveal that the Petunia lineage has experienced at least two rounds of hexaploidization: the older gamma event, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
339
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 331 publications
(377 citation statements)
references
References 49 publications
20
339
1
6
Order By: Relevance
“…Many angiosperm plants have experienced extensive duplication of these regulatory genes. The amplification of MYB genes belonging to subgroup 6 that regulate anthocyanin biosynthesis may be a general mechanism underlying the diversity of floral pigmentation patterns, as observed in Petunia (Bombarely et al, 2016) and Antirrhinum (Schwinn et al, 2006), but also might be the result of domestication and human selection, as proposed for grape (Matus et al, 2008). In Citrus, the presence of no more than one functional MYB regulator suggests that the production of anthocyanins is not under strong selective pressure and is largely dispensable.…”
Section: Discussionmentioning
confidence: 97%
“…Many angiosperm plants have experienced extensive duplication of these regulatory genes. The amplification of MYB genes belonging to subgroup 6 that regulate anthocyanin biosynthesis may be a general mechanism underlying the diversity of floral pigmentation patterns, as observed in Petunia (Bombarely et al, 2016) and Antirrhinum (Schwinn et al, 2006), but also might be the result of domestication and human selection, as proposed for grape (Matus et al, 2008). In Citrus, the presence of no more than one functional MYB regulator suggests that the production of anthocyanins is not under strong selective pressure and is largely dispensable.…”
Section: Discussionmentioning
confidence: 97%
“…3). Furthermore, comparison of ;120 kb of genomic sequence surrounding the SlASAT1 and Pax36474 loci (Tomato Genome Consortium, 2012;Bombarely et al, 2016) revealed considerable synteny between tomato and P. axillaris within this region, suggesting that the genes are orthologous (Supplemental Fig. S1).…”
Section: Identification Of Putative Asats From P Axillarismentioning
confidence: 99%
“…The four candidate P. axillaris ASATs are highly divergent at the nucleotide level, and it was possible to identify fragments of each gene ranging from 247 to 375 nucleotides in length that are highly specific for each target. For example, BLASTN searches against P. axillaris transcriptome and genome assemblies (Guo et al, 2015;Bombarely et al, 2016) failed to identify any additional nucleotide sequences longer than 19 bp that share 100% identity with each VIGS fragment, indicating that there is very limited potential for off-target silencing. Upon silencing, the abundance of each target transcript was reduced by approximately 80% to 90% in silenced lines when compared with those of TRV2 empty vector controls (Supplemental Fig.…”
Section: Silencing Of Putative Asats In P Axillarismentioning
confidence: 99%
“…However, there are a variety of reasons that a genome sequence may have particular importance. It may belong to a species that has been extensively used as a model organism, such as petunia 1 …”
mentioning
confidence: 99%
“…The PacBio system can now stably generate long-reads at an average length of over 10 kilobases, and has been combined with short-read sequencing in many genome projects. For example, the Petunia axillaris genome 1 , rose genome and fern genomes all benefited from this technology. The addition of PacBio longreads dramatically improved genome contiguity and resulted in contig N50 size approximating or even exceeding the megabase (Mb) level.…”
mentioning
confidence: 99%